A Data-Driven Approach to Running Gait Assessment Using Inertial Measurement Units - Erin Ross MS; Anthony Milian MS; Mason Ferlic MSE; Samuel Reed BS, ATC; Adam S. Lepley PhD, ATC (SAGE Publishing, 2022)
Background: Running is an extremely common exercise, both recreationally and competitively. Combined with clinical assessment, technology-driven biomechanical gait analysis can be used to examine markers of performance and injury risk in runners. Indications: The indication is to provide clinicians and sports science researchers a framework for using inertial measurement units (IMU) for data-driven, quantitative gait assessments. Technique Description: This video details practical application of IMU use in biomechanical gait assessments. Details on participant and equipment setup, in-session protocols, and selection of gait variables are included. Results: Following collection of demographic and anthropometric outcomes, IMUs should be placed on rigid segments of the lower extremity, sacrum, and trunk. In our model, we place IMUs on the foot, shank, thigh, sacrum, and lower thoracic spine. Following static anatomical calibration, running gait biomechanics are evaluated at multiple speeds using IMUs, 2-dimensional high-speed video cameras, and an instrumented treadmill. The high-speed video and IMU data are analyzed together at various parts of the gait cycle, including foot strike, mid-stance, toe-off, and flight. Many kinematic and kinetic variables (ie, unilateral discrete joint angles, joint excursions, joint moments, spatiotemporal outcomes, etc) can be selected for analysis, ideally via a collaboration between the sports science, athletic, and sports medicine teams. A collaborative approach should also be used to determine how this information will be used to alter training programs or influence injury risk in the running athlete. Discussion/Conclusion: This report details how to use a data-driven approach to evaluate running gait biomechanics using IMU technology. This framework for gait analysis is most applicable, and effective, when the team of researchers works in conjunction with coaches, sport scientists, and athletes. Utilizing this framework, training can be adapted based on the objective and clinical assessment to reduce injury risk and improve performance in the gait assessment.